2016
DOI: 10.31983/keslingmas.v35i4.3103
|View full text |Cite
|
Sign up to set email alerts
|

DESKRIPSI BIONOMIK NYAMUK Anopheles Sp DI WILAYAHKECAMATAN PARIGI KABUPATEN PANGANDARAN PROVINSI JAWA BARAT TAHUN 2016

Abstract: Kondisi Desa Cibenda yang berada di dataran rendah dan berbatasan langsung dengan pantai yang menjadi muara sungai dan perairan Samudera Indonesia memungkinkan nyamuk Anopheles Spp untuk berkembangbiak, karakteristik umum habitat yang ditemukan adalah berupa rawa-rawa, kolam bekas tambak udang, lahan pertanian atau persawahan yang mendominasi juga habitat ideal bagi beberapa nyamuk Anopheles lain. Dengan metode observasional menggambarkan atau mengamati bionomik nyamuk Anopheles Spp di wilayah Kecamatan Parigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A number of Anopheles spp. breeding sites were discovered in ponds near rivers and springs [11][12][13][14][15][16][17][18]. Study in West Java showed An.vagus breeding habitat of An.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of Anopheles spp. breeding sites were discovered in ponds near rivers and springs [11][12][13][14][15][16][17][18]. Study in West Java showed An.vagus breeding habitat of An.…”
Section: Resultsmentioning
confidence: 99%
“…aconitus and An. vagus live in rice fields [12]. Many studies of malaria vector showed the habitat of Anopheles are from mountains, forest, and coastal areas [19].…”
Section: Resultsmentioning
confidence: 99%
“…A number of Anopheles spp. mosquito breeding sites were discovered in ponds near rivers and springs [20][21][22][23][24][25][26][27]. There is colleration betweeen breeding habitat with the abiotics factor in the environment A study showed that habitats with An.…”
Section: The Biodiversity Of Anopheles As Malaria Vector In Indonesiamentioning
confidence: 99%
“…vagus live in rice fields and abandoned shrimp ponds, and there are many streams sandcovered river (lagoon) which is breeding places for An. sundaicus mosquitoes [21].…”
Section: The Biodiversity Of Anopheles As Malaria Vector In Indonesiamentioning
confidence: 99%
“…vagus lebih suka berada di luar rumah dan menggigit di waktu senja sampai dengan dini hari (eksofagik). 25,26,27,28 Puncak aktivitas An. vagus menghisap darah dilapangan berbeda-beda yaitu terjadi pada pukul 22.00-23.00 (Kabupaten Kupang, NTT), 29 02:00-03:00 (Aceh).…”
Section: Pembahasanunclassified